(untitled) (Historia, 2021)
The long sojourn in South Africa shaped Gandhiji's life in myriad ways, giving him, above all, the mission of his life and the methodology to fulfil it. The fight against oppression and exploitation, and the development of the Satyagraha as a political and moral weapon contributed to his transformation into a Mahatma (the great soul) - and eventually "the Father of the (Indian) Nation".